Model of Pollutant Dispersion in the Atmosphere Through the Giadmt Technique - Costa, Camila P.; Vilhena, Marco T.; Tirabassi, Tiziano; Moreira, Davidson M. (Ciência e Natura, 2007)
Model of pollutant dispersion in the atmosphere through the GIADMT technique.